BAFF/APRIL pathway in Sjögren syndrome and systemic lupus erythematosus: relationship with chronic inflammation and disease activity - A. Rigon (Reumatismo, 2011)
Objectives: BAFF and APRIL belong to the tumor necrosis factor (TNF) superfamily and are crucial for the survival, maturation, and differentiation of B cells. Aim of the study is to evaluate BAFF and APRIL in patients affected by Sjögren syndrome (SS) and systemic lupus erythematosus (SLE). Methods: Sixty patients, (40 SLE, 20 SS) and 20 healthy subjects were enrolled in this study. All subjects were evaluated for laboratory data (ESR, CRP, immunoglobulin G, A and M, complement fragments C3 and C4, LDH, beta2microglobulin, serum levels of rheumatoid factor), autoantibodies (ANA; ENA-SSA, -SSB, -Sm) and lymphocytes subpopulations. For patients, disease activity and damage indexes were assessed with the use of SLEDAI and SLICC and SSDAI and SSDDI for SLE and SS, respectively. BAFF and APRIL were determined by commercial sandwich ELISA kit (R&D Systems, Bender MedSystem). Statistical analysis has been performed with software Prism (Graphpad Instat, version 5.00). Results: APRIL levels were higher among SLE and SS patients compared to controls (p<0.0001, and p0.0001, respectively). BAFF levels in SLE were significantly higher than in SS (p<0.0001). We found higher BAFF levels in SLE and SS compared to controls (p<0.0001). Among SLE patients APRIL correlated with SLEDAI (r 0.3, p 0.04), SLICC (r 0.5,p 0.001), ESR (r 0.3, p 0.005) and CRP (r 0.4, p 0.02). Among SS patients APRIL correlated with SSDAI (r 0.4, p 0.02), SSDDI (r 0.4, p0.01), IgG (r 0.5, p0.01), ESR (r 0.6, p 0.01), CRP (r 0.6, p 0.02) and CD19 B lymphocytes absolute count (r 0.4, p 0.04); BAFF correlated with SSDDI (r 0.7, p 0.004) and CD19 B lymphocytes absolute count (r 0.5, p 0.04). Conclusions: In this study we showed a correlation between disease activity, damage indexes and BAFF/APRIL levels in SLE and SS patients suggesting a role in the strong activation of the immune system in patients with active disease.